1982
DOI: 10.1042/bj2080047
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the stimulation of dolichol-mediated glycosylation by dexamethasone in HeLa cells

Abstract: The effect of the addition of luM-dexamethasone on the temporal sequence of the glycosylation process has been studied in HeLa S3G cells. In the presence of delipidized serum, dexamethasone caused an increase in 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase and an accelerated synthesis of dolichols. These events were followed by an increase in the transfer of mannose from GDP-mannose to mannolipid.An increase in the rate of synthesis of lipid-linked oligosaccharides and a stimulation of glycosylation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A stimulatory effect of dexamethasone on the synthesis of certain classes of secretory glycoproteins has been reported by Baumann et al (1983) in hepatoma tissue-culture cells and in primary hepatocyte culture. Furthermore, increased formation of dolichol-linked sugar derivatives by dexamethasone has been shown in HeLa cells (Ramachandran et al, 1982). The results given in the present paper are complementary to those observations.…”
supporting
confidence: 81%
“…A stimulatory effect of dexamethasone on the synthesis of certain classes of secretory glycoproteins has been reported by Baumann et al (1983) in hepatoma tissue-culture cells and in primary hepatocyte culture. Furthermore, increased formation of dolichol-linked sugar derivatives by dexamethasone has been shown in HeLa cells (Ramachandran et al, 1982). The results given in the present paper are complementary to those observations.…”
supporting
confidence: 81%
“…It appears that, like compactin and (-)-hydroxycitrate, dexamethasone very rapidly gives rise to opposing changes in these activities, whereas the rate of fatty acid synthesis was unchanged ( Table 1). In contrast, in HeLa cells, there is a lag period of 12-16h before the effect of dexamethasone on HMG-CoA reductase activity becomes apparent (Cavenee & Melnykovych, 1977;Ramachandran et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Since our early studies have demonstrated a glucocorticoid-stimulated increase in alkaline phosphatase (Melnykovych, 19621, an enzyme which could be involved in the degradation of both dolichol phosphate and retinol phosphate, a study of the effects of both glucocorticoids and vitamin A compounds on the levels of activity of alkaline phosphatase seemed indicated. It is noteworthy that glucocorticoids, in addition to their effects on alkaline phosphatase, also increase the levels of cellular dolichols and dolichylmannolipids (Ramachandran et al, 1981, Ramachandran et al, 1982.…”
mentioning
confidence: 99%